(untitled) (Research, Society and Development, 2019)
The present study aims to evaluate the relationship between selenium plasma concentration and cardiovascular risk in obese women. This is a case-control study, involving 67 women, aged between 20 and 50 years, and divided into two groups: control group (eutrophic women, n = 42) and case group (obese women n = 25). Plasma selenium and lipid profile (total cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol and VLDL-cholesterol) were analyzed. Data were analyzed using the SPSS for Windows 22.0 statistical program. The project was approved by the Research Ethics Committee of the Federal University of Piauí, under opinion number 2.014.100. Regarding the results, lower concentrations of plasma selenium were observed for the obese group, with a statistically significant difference between the groups (p <0.001). At the same time, higher concentrations of total cholesterol, HDL-cholesterol, LDL-cholesterol, and Castelli I and II indices were found among obese women compared with eutrophic women, with a statistically significant difference (p <0.05). For the result of the correlation analysis between the variables, it was found that there was a moderate negative correlation between plasma selenium, total cholesterol and LDL-cholesterol (p <0.05). Before the results obtained, the study shows the likely influence of selenium on lipid profile parameters and, consequently, on the reduction of cardiovascular risk, such as the inverse relationship evidenced between plasma mineral concentration, total cholesterol and LDL-cholesterol.